2021
DOI: 10.3390/antibiotics10091087
|View full text |Cite
|
Sign up to set email alerts
|

Does Vancomycin Wrapping in Anterior Cruciate Ligament Reconstruction Affect Tenocyte Activity In Vitro?

Abstract: Knee septic arthritis is a devastating complication following anterior cruciate ligament (ACL) reconstruction. To prevent this issue, intraoperative soaking of ACL grafts with vancomycin is often performed before implantation. Although vancomycin cytotoxicity has been reported several times, little is known about its biological effect on tenocytes. The aim of this study was to evaluate the in vitro effects of vancomycin on human primary tenocytes (hTCs). hTCs were isolated from hamstring grafts of four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Xiao et al 31 exposed human patellar tenocytes to five different concentrations of vancomycin solution for three time durations and demonstrated no notable cell death or toxicity even in concentrations up to 12,800 μg/mL for 2- and 6-hour exposures. However, Papalia et al 32 investigated the effects of vancomycin on human tenocytes derived from hamstring grafts harvested from four patients during ACL reconstruction and measured in vitro effects on metabolic activity, cell toxicity, and apoptosis. The authors concluded that tenocytes remain unaffected at a concentration of 2.5 mg/mL and is safe for up to 1 hour, but cytotoxicity was detected with a 10 mg/mL solution after 15 minutes and at all higher concentrations.…”
Section: Vancomycin-treated Acl Graftsmentioning
confidence: 99%
“…Xiao et al 31 exposed human patellar tenocytes to five different concentrations of vancomycin solution for three time durations and demonstrated no notable cell death or toxicity even in concentrations up to 12,800 μg/mL for 2- and 6-hour exposures. However, Papalia et al 32 investigated the effects of vancomycin on human tenocytes derived from hamstring grafts harvested from four patients during ACL reconstruction and measured in vitro effects on metabolic activity, cell toxicity, and apoptosis. The authors concluded that tenocytes remain unaffected at a concentration of 2.5 mg/mL and is safe for up to 1 hour, but cytotoxicity was detected with a 10 mg/mL solution after 15 minutes and at all higher concentrations.…”
Section: Vancomycin-treated Acl Graftsmentioning
confidence: 99%
“…After ACL surgery, 63-65% of patients return to sport, with 44-46% returning to competitive participation. [28] . Those who failed the six-month return-to-sport test showed altered contralateral hip strategy with restricted motion and attenuating forces about the damaged knee during locomotion.…”
Section: Final Postoperative Obstaclesmentioning
confidence: 99%
“…and prolonged rehabilitation. Nonetheless, autografts still remain the 'gold standard' in primary ACLR [3]. Therefore, a great interest towards the development of synthetic anterior cruciate ligament (ACL) grafts that may overcome such drawbacks has been raised in the last decades.…”
Section: Introductionmentioning
confidence: 99%